Examining Rumor Dissemination and Information Equivocality in Social Media Behavior - Angga Pandu Wijaya; Widya Prananta; Bogy Febriatmoko (ETTISAL : Journal of Communication, 2023)
This research aims to analyze the impact of rumor dissemination and information equivocality on discontinuance behavior when influencers face negative rumors. As an influencer's follower count decreases, their credibility weakens, thereby reducing the effectiveness of product representation through brand ambassadors. The study adopted a quantitative approach with a purposive sampling criteria, comprising a total sample size of 191 participants. The test results indicate that rumor dissemination does not significantly affect social media fatigue, while information equivocality does influence it. Additionally, the study demonstrates a positive association between rumor dissemination, information equivocality, and discontinuance behavior. Social media fatigue does not mediate the effect of rumor dissemination on discontinuance behavior; however, information equivocality partially mediates this relationship. The study highlights the relevance of the agenda-setting theory when influencers face negative rumors and information equivocality. In conclusion, negative rumors contribute to a decrease in followers due to rumor dissemination and information equivocality on social media.